Direct Synthesis of Graphdiyne Nanowalls on Arbitrary Substrates and Its Application for Photoelectrochemical Water Splitting Cell. Issue 9 (23rd December 2016) - Gao, Xin; Li, Jian; Du, Ran; Zhou, Jingyuan; Huang, Mao‐Yong; Liu, Rong; Li, Jie; Xie, Ziqian; Wu, Li‐Zhu; Liu, Zhongfan; Zhang, Jin
Abstract : A general and simple route to fabricate graphdiyne nanowalls on arbitrary substrates is developed by using a copper envelope catalysis strategy. The GDY/BiVO4 system is but one example of combing the unique properites of GDY with those target substrates where GDY improves the photoelectrochemical performance dramatically.